The role of intellectual property in the development of underutilized crops - Alcock, Harriette (2021)
This research is focused upon the availability and suitability of intellectual property protection for developments in underutilized crop species. It has been suggested that intellectual property protection should be a positive tool for addressing food security concerns, by incentivizing innovation and rewarding breeders. Equally, access and benefit sharing mechanisms, which exist to regulate access to genetic material and redistribute the benefits arising from its use, also play a significant role in the development of new crop species. Thus, this research explores the extent to which states are obliged to provide intellectual property protection for plant-based innovations, and whether these are compatible with developments in underutilized crop species. It also considers the overlap between systems of intellectual property protection and access and benefit sharing regimes. This is explored by examining the relevant international norms pertaining to intellectual property protection (the Agreement on Trade Related Aspects of Intellectual Property and the Conventions of the International Union for the Protection of New Varieties of Plants) and the regulation of access to genetic resources (the Convention on Biological Diversity and its Nagoya Protocol, the International Treaty on Plant Genetic Resources for Food and Agriculture). This is developed by exploring how the principles derived from these regimes relate to one another and by drawing upon examples developed in distinct jurisdictions. The research considers Malaysia not only as a genetically rich state that is reliant upon external inputs to meet national food security, but one that is host to research and development activities involving underutilized crop species. It is focused upon analysing the models of intellectual property protection and access and benefit sharing that have been implemented in Malaysia and evaluating their utility for innovations in underutilized crops by incorporating the perspectives of stakeholders in underutilized crops and comparing the aspects of the Malaysian approach with alternatives. It concludes by analysing whether in this context, intellectual property protection it is likely to be a useful tool for addressing food security concerns.